Motion Sensing Techniques For Mobile Phone User Interface Design - Chen, Lim Kok (2009)
The main intentions of this thesis are to study the existing camera-based motion sensing techniques and to propose an efficient camera-based motion sensing technique for mobile phones user interaction design.